Formulasi Masker Gel Peel Off dari Kulit Pisang Ambon (Musa Paradisiaca Var): Peel Off Mask Formulation from Ambon Banana Peel (Musa paradisiaca var) - Dwi Fitrah Wahyuni; Mardiah Mustary; Syafruddin Syafruddin; Deviyanti Deviyanti (Jurnal Sains dan Kesehatan, 2022)
Peel off face mask is one type of face mask that has advantages in its use, namely that it can be easily removed or lifted like an elastic membrane. The purpose of this study was to determine the formulation of a peel off gel mask preparation made from Ambon banana peel (Musa paradisiaca var). The gel mask formulation was made on the basis of Polyvinyl Alcohol (PVA) with a concentration of 7%. The active ingredient used is Ambon banana peel which contains vitamin B6, carbohydrates, phosphorus, protein, vitamin C, and several other substances that are useful for body health and beauty as well as other ingredients such as flavonoids, tannins, and saponins. This study used experimental methods to determine the best proportion of masks from Ambon banana peels which included organoleptic tests, homogeneity, drying time, pH and dispersion. The results of the observations were organoleptic test with a characteristic brown odor and semi-solid form, homogeneity test from day 1/14 for all homogeneity formulas, pH test from day 1/14 all formulas had a good pH because they were still in range 4.5-6.5 which is 5, the dry preparation test on the 1st/14th day formula 1, 2 has good drying power because it is still in the drying time requirement of 15-30 minutes while formula 3 has a high drying power. less good than the 1st/14th day because it exceeded the drying time of the preparation, and the dispersion test on day 1 of formulas 1 and 2 met the requirements while formula 3 did not meet the requirements while on day 14 all formulas met the requirements From the results of the research that has been done, it can be concluded that the Ambon banana peel can be formulated into a peel off gel mask preparation.